2019
DOI: 10.1177/0278364919870227
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial discriminative sim-to-real transfer of visuo-motor policies

Abstract: Various approaches have been proposed to learn visuo-motor policies for real-world robotic applications. One solution is first learning in simulation then transferring to the real world. In the transfer, most existing approaches need real-world images with labels. However, the labelling process is often expensive or even impractical in many robotic applications. In this paper, we propose an adversarial discriminative sim-to-real transfer approach to reduce the cost of labelling real data. The effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…However, policies trained using simulations often do not transfer for real world tasks since the reality gap between simulations and the physical world are strongly pertinent. These issues of RL have been tackled using techniques such as actuator modeling [15], implementing a modular training approach [16], introducing domain randomization [17], increasing policy generalization [18] and adding noise to observations and actions in the training environments. Authors of [15] have demonstrated the use of a deep RL approach to complex legged locomotion tasks.…”
Section: A Related Workmentioning
confidence: 99%
“…However, policies trained using simulations often do not transfer for real world tasks since the reality gap between simulations and the physical world are strongly pertinent. These issues of RL have been tackled using techniques such as actuator modeling [15], implementing a modular training approach [16], introducing domain randomization [17], increasing policy generalization [18] and adding noise to observations and actions in the training environments. Authors of [15] have demonstrated the use of a deep RL approach to complex legged locomotion tasks.…”
Section: A Related Workmentioning
confidence: 99%
“…This sim-to-real transfer problem has recently been tackled by numerous research groups. Earlier approaches mainly highlight the issues around this transfer [15], with more recent efforts proposing solutions, including domain adaptation and Generative Adversarial Networks (GAN) which requires both real world and simulated data [3]. Results showing the early promise of these techniques -using domain adaptation, Bousmalis et al [16] were able to achieve a success rate for real world grasping trained in simulation of 76.7% on a dataset of unseen objects.…”
Section: A Bridging the Reality Gapmentioning
confidence: 99%
“…This was recently applied to sim-to-real transfer for a robotic table-top-reaching task with a 7 DoF arm [8]. The authors show the ability to effectively transfer the learning of a visuomotor policies from a simulation environment to the real setup by the use of very few real expert demonstrations for fine-tuning.…”
Section: ) Learning the Mapping Between Simulation And Realmentioning
confidence: 99%